Model-based optimization of axisymmetric wave motion in buried plastic water distribution pipes - Scussel, O. [UNESP]; Brennan, M. J. [UNESP]; Muggleton, J. M.; Almeida, F. C. L. de [UNESP]; Paschoalini, A. T. [UNESP]; Desmet, W.; Pluymers, B.; Moens, D.; Rottiers, W. (Katholieke Univ Leuven, Dept Werktuigkunde, 2018)
This paper describes a model-based technique to determine the bulk and shear modulus of the soil from measured leak noise data, assuming that the pipe properties are known. Two water pipe systems which have different soil properties are considered: one is in the UK and the other one is in Brazil. The UK pipe system has sandy soil, where both compressional and shear wave propagate away from the pipe. The Brazilian pipe system has clay-like soil and only shear wave propagates away from the pipe. The results, based on optimising the soil properties to give a best fit for the leak noise speed and its attenuation, give soil properties that fall within the expected range for the different locations. These results are helpful in determining the fundamental limitations of acoustic correlators in various situations.